Studi Fitoremediasi Merkuri Pada Tailing Amalgamasi Penambangan Emas Rakyat Menggunakan Akar Wangi (Vetiveria zizanioides L.) - Arofah, Nurmaya; Erusani, A. Silvan; Azahra, Fabika (Universitas Riau, 2024)
Heavy metal pollution in the soil has become a global problem along with the industrialization process, mining, and laboratory activities, as well as daily activities. Artisanal and small-scale gold mining (ASGM) activities using amalgamation methods have the potential to pollute the environment because they produce tailings with mercury (Hg) metal content, which causes various environmental problems even though they are in very low concentrations. The purpose of this study was to determine the characteristics of tailings polluted with Hg metal, determine Hg levels in soils that have been absorbed by Vetiveria zizanioides, determine the effect of compost addition on soil quality improvement, and determine the factor of mercury transfer from soil to plants. The results showed that the mercury concentration in amalgamation tailings of 201.6 mg/kg may decrease after 28 days of remediation to 13.72 mg/kg at TTG1, 170.73 mg/kg at TTG2, and 53.4 mg/kg at TTG3. The ability of Vetiveria zizanioides L. to absorb mercury in amalgamated tailings without adding compost can be seen from the TTG1 transfer factor value of 9.69.